Crypto-coding technique based on polar code and secret key generated from wireless channel characteristics for wireless communication systems. - Dinh Van Linh; Vu Van Yem; Hoang Thi Phuong Thao (PLoS ONE)
The crypto-coding technique is essential for modern digital wireless communications systems, allowing data encryption and channel coding to be performed in only one step without requiring additional hardware. This work proposes a crypto-coding technique combining polar codes with a secret key, which is derived from wireless channel characteristics, to boost the security and reliability characteristics of the systems. The secret key is divided into two parts, one is assigned to the frozen bits, and the other is XORed with the information bits. A simulation with different key lengths and code lengths is carried out in Additive white Gaussian noise (AWGN) that helps us to evaluate this technique by the error correction and security performance, computational complexity. The key benefit is that it achieves the same bit error rate (BER) performance and computational complexity as traditional polar codes and existing methods despite only taking one step. Meanwhile, it ensures completely degraded decoding effectiveness at eavesdroppers, thus it is effective against passive eavesdropping attacks. Furthermore, this method does not require additional hardware overhead for key management and distribution.